Teneurin C-terminal associated peptides (TCAP): modulators of corticotropin-releasing factor (CRF) physiology and behavior - Chen, Yani; Xu, Mei; De Almeida, Reuben; Lovejoy, David (Frontiers in Neuroscience, 2013)
The existence of the teneurin C-terminal associated peptides (TCAP) was reported in 2004 after screening a rainbow trout hypothalamic cDNA for corticotropin-releasing factor (CRF)-related homologs. In vertebrates, there are four TCAP paralogs, where each peptide is associated with a teneurin transmembrane protein. The TCAPs are 40 or 41 amino acids in length and possess less than 20% residue identity with the CRF family of paralogs. Orthologs of TCAP are found in all metazoans with the possible exception of poriferans and cnidarians. Recent evidence indicates that TCAP and the teneurins may have been introduced into the Metazoa via horizontal gene transfer from prokaryotes into a basal protistan. Thus, the origin of the TCAPs likely predated that of the CRF family. In the mammalian brain, TCAP-1 is transcribed independently from teneurin-1. Moreover, TCAP-1 acts on neurons by a CRF-receptor independent signal transduction pathway to regulate cellular cytoskeletal function to stimulate cell activity. Administration of synthetic TCAP-1 to rodents inhibits a number of CRF- and stress-associated behaviors via a hypothalamic-pituitary-adrenal (HPA) axis-independent mechanism.